The ‘Real-World Approach’ and Its Problems: A Critique of the Term Ecological Validity - Holleman, Gijs A.; Hooge, Ignace T. C.; Kemner, Chantal; Hessels, Roy S. (Frontiers in Psychology, 2020)
A popular goal in psychological science is to understand human cognition and behavior in the ‘real world’. In contrast, researchers have typically conducted their research in experimental research settings, a.k.a. the ‘psychologist’s laboratory’. Critics have often questioned whether psychology’s laboratory experiments permit generalizable results. This is known as the ‘real-world or the lab’-dilemma. To bridge the gap between lab and life, the concept of ecological validity has been widely used to evaluate whether laboratory experiments resemble and generalize to the ‘real world’. However, researchers seldom define what they mean with this concept, nor are there any guidelines or criteria available for evaluating a study’s ecological validity. In our view, the popular concept of ecological validity is ill-formed, lacks specificity, and falls short of adequately addressing the fundamental problem of generalizability. In order to move beyond this ‘real-world or the lab’-dilemma, we believe that researchers should be more specific about the contexts of behaviors they are interested in, instead of aiming to understand human cognition and behavior in the ‘real world’. We argue that this is a more constructive way of uncovering the context-specific and context-generic principles of human cognition and behavior.